Precision in Progress: The Crucial Nexus of Instrumentation and Measurement in Biotechnology Advancements - Ushaa Eswaran; Vishal Eswaran (International Journal of Molecular Biotechnological Research, 2023)
This comprehensive review examines the critical importance of instrumentation and measurement technologies in enabling advances across diverse domains of modern biotechnology. Detailed examples are provided demonstrating how analytical tools empower quantitative biology, drive discoveries, catalyze innovations, and provide solutions to global challenges. The historical evolution of bioanalytical techniques is traced, highlighting milestones that unleashed new capabilities. Current trends and future outlook are explored, underscoring the ongoing pivotal need for precision measurement capabilities to continue pushing frontiers of biotechnology forward
Keywords: AI Integration; Analytical Techniques; Automation; Biosensors; Emerging Trends; Genomics; Instrumentation; Measurement Technologies; Molecular Engineering; Point-Of-Care Diagnostics; Single-Cell Analysis; Synthetic Biology; Wearable Sensors; biotechnology; microfluidics